American Trotskyist: The Heritage of James P. Cannon. - Ansel, Corey (American Communist History, 2015)
The essay discusses United States' political history. Topics of the essay include political leader James P. Cannon, Trotskyism and communism in United States. Other topics such as Tsarism in Russia, Bolshevik Revolution and World War I are also discussed in the essay. Great Depression and communist movements are mentioned.